Energy Potential of Elephant Camp: The Preliminary Study of Maewin sub district, Chiang Mai, Thailand - Pooya, Tidarak; Pan-in, Sopee; Sintuya, Hathaithip; Sawatdeenarunat , Chayanon (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
This research aims to examine the energy potential of the elephant camps located in Tumbon Maewin, Apmphoe Maewang, Chiang Mai, Thailand.A questionnaire survey was given to the research participants. The questions mainly focused on the energy consumption, monthly budget for buying energy, and their understanding on energy. The results from the participants in 16 elephant camps, handling 133 animals, indicated that the camps paid more than 3000, 10000, and 400 baths in average monthly for electricity, fuel oil, and cooking gas, respectively. However, the generated elephant dung of 4 tons per day has the gross and net heating values of 63600 and 58600 MJ which can be used as a renewable resource to produce renewable energy for replacing the fossil fuels serving the elephant camp activities.